Risiko Produksi Dan Harga Pada Usahatani Rumput Laut Di Kabupaten Takalar Provinsi Sulawesi Selatan - Alfira Yanamisra; Anna Fariyanti; Anisa Dwi Utami (Forum Agribisnis, 2023)
Seaweed is an export product of aquaculture commodities that have high economic value. One of the areas with high seaweed production in Indonesia is Takalar Regency, South Sulawesi Province. The challenges faced in seaweed farming in South Sulawesi are productivity and price fluctuations. This indicates that there is a risk in cultivated seaweed farming. This study aimed to analyze production risk factors, price risk levels, and risk management for seaweed farming in Takalar Regency, South Sulawesi Province. This study uses primary data derived from 100 respondents who were selected randomly. Analysis of production risk factors using the Just and Pope models with the Cobb-Douglas production function and the level of price risk is carried out by measuring the coefficient of variation and the price floor. Meanwhile, risk management consists of preventive, mitigation, and risk-coping strategies. The results showed that the production risk factors that had a significant effect was labor and harvesting age and had the characteristic of inducing risk factors. The price risk farmers face in Takalar Regency is indicated by the coefficient variation value of 0,279, so the risk level faced is 27,9 percent per kg. Risk management is a preventive strategy by maximizing farming activities, and the quality of the inputs used before risks occur in production and prices.